Influence of the chronic stress of pregnant rats on their offspring's morpho-functional liver condition - O. Nikolayeva; M. Kuznetsova; O. Lytvynenko (Kazimierz Wielki University, 2019)
The morphofunctional state of the rats offspring liver, born from femal rats underwent chronic immobilization stress during pregnancy was studied. It has been revealed that chronic stress in female rats during pregnancy wields considerable influence over liver morphology and lipid-synthesizing function of their offspring. Pronounced discomplexing of the beam-radiary structure, increase of stromal - parenchymal index due to increase in stromal and decrease in the parenchymal components of the liver and decrease level of expression of endothelial synthase has been morphologically revealed. Biochemical study of the liver homogenate revealed signs of impaired synthesis, secretion and reuptake of lipids (increase of cholesterol, tryglyceerids and non-esterified fatty acids and decrease of phospholipids. In the offsprings blood serum dyslipidemia (increase of cholesterol and low-density lipoproteins level) was detected. All this is a risk factor for fibrosis, fatty hepatosis and level cirrhosis development.